THE SIGNIFICANCE OF PHYSICAL ACTIVITY IN SUPPORTING MENTAL HEALTH - Axtamov Djamshed Baxromovich (Web of Journals Publishing, 2025)
This paper explores the crucial role of physical activity in promoting and maintaining mental health. It highlights how regular exercise can reduce symptoms of stress, anxiety, and depression while enhancing mood, cognitive function, and overall emotional well-being. The study also discusses the biological and psychological mechanisms through which physical activity positively impacts mental health and offers practical recommendations for incorporating exercise into daily routines.
Keywords: Physical Activity, Mental Health, Stress Reduction, Anxiety, Depression, Cognitive Function, Emotional Well-being, Exercise Benefits.